Assessment of trunk microtensiometer as a novel biosensor to continuously monitor plant water status in nectarine trees - Conesa, María R.; Conejero, Wenceslao; Vera, Juan; Ruiz-Sánchez, Ma Carmen (Frontiers in Plant Science, 2023)
The objective of this work was to validate the trunk water potential (Ψtrunk), using emerged microtensiometer devices, as a potential biosensor to ascertain plant water status in field-grown nectarine trees. During the summer of 2022, trees were subjected to different irrigation protocols based on maximum allowed depletion (MAD), automatically managed by real-time soil water content values measured by capacitance probes. Three percentages of depletion of available soil water (α) were imposed: (i) α=10% (MAD=27.5%); (ii) α=50% (MAD=21.5%); and (iii) α=100%, no-irrigation until Ψstem reached -2.0 MPa. Thereafter, irrigation was recovered to the maximum water requirement of the crop. Seasonal and diurnal patterns of indicators of water status in the soil-plant-atmosphere continuum (SPAC) were characterised, including air and soil water potentials, pressure chamber-derived stem (Ψstem) and leaf (Ψleaf) water potentials, and leaf gas exchange, together with Ψtrunk. Continuous measurements of Ψtrunk served as a promising indicator to determine plant water status. There was a strong linear relationship between Ψtrunk vs. Ψstem (R2=0.86, p<0.001), while it was not significant between Ψtrunk vs. Ψleaf (R2=0.37, p>0.05). A mean gradient of 0.3 and 1.8 MPa was observed between Ψtrunk vs. Ψstem and Ψleaf, respectively. In addition, Ψtrunk was the best matched to the soil matric potential. The main finding of this work points to the potential use of trunk microtensiometer as a valuable biosensor for monitoring the water status of nectarine trees. Also, trunk water potential agreed with the automated soil-based irrigation protocols implemented.